Diabetic Ketoacidosis in Type 1 Diabetes Mellitus - Lukman Nurhakim; Rudy Afriant; Dinda Aprilia (Talenta Publisher, 2024)
Background: Diabetic ketoacidosis (DKA) is a state of metabolic decompensation/disorder characterized by the triad of hyperglycemia, acidosis and ketosis, caused by absolute or relative insulin deficiency and increased counter-regulatory hormones. Objective: To report a case of diabetic ketoacidosis (DKA) in a young adult patient with type 1 diabetes mellitus and scalp abscess, emphasizing the importance of early diagnosis and prompt management to achieve clinical improvement. Methods: This case report describes the clinical presentation, diagnostic approach, and therapeutic management of a 19-year-old male with DKA. Results: A 19-year-old male treated in the internal medicine ward of Dr. M djamil Padang with diabetic ketoacidosis, type 1 DM, and Abscess capitis. The patient was treated with rehydration and intravenous insulin infusion can show clinical improvement. Conclusion: The diagnosis in patients is based on anamnesis, physical examination and supporting examinations. Immediate therapy is needed in the management of DKA in patients. After DKA is resolved, look for the causes of the risk of DKA. On the third day of treatment the patient's condition improved clinically and the laboratory.